A new method for the construction of solutions of nonlinear wave equations - Barannyk, A. F.; Yuryk, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We propose a simple new method for the construction of solutions of multidimensional nonlinear wave equations.